Accounting Ethics Courses, Teaching Styles, Ethical Culture and Ethical Behaviour of Accounting Graduates in Malaysia - Nurul Nazlia Jamil; Dato' Hasnah Hj Haron; Nathasa Mazna Ramli; Fatin Arissa Parsimin; Zalailah Salleh (UITM, 2024)
Indexed by Scopus